Repositioning the Nigerian Lawyer Through Mandatory Continuing Legal Education: Developing a Cross-Border Approach to Legal Education - Uche Nnawulezi; Hilary Nwaechefu (The Indonesian Journal of International Clinical Legal Education, 2022)
The main aim of the article is to examine how the Nigerian lawyer will be better equipped through mandatory continuing legal education with regards to developing a cross- border approach to legal education in Nigeria. The article revealed the shortcomings of legal education in Nigeria and compared them with other legal education system around the globe. The article addressed three core questions that are particularly relevant to the Nigerian lawyer: (1) who is considered a Nigerian lawyer under the Nigerian legal practitioners Act? Approaching this question allows examination of the relevant sections of the legal practitioners Act. The second and third questions addressed two issues that are crucial to the practice of law in Nigeria (2) how is the practice of law regulated? (3) Are there provisions for mandatory continuing legal education for the Nigerian lawyers? This approach revealed that there are provisions for mandatory continuing legal education in Nigeria, but in practice, it appears only to be figment of imagination. However, the article adopted a diagnostic approach based on a review of literatures and evidence-based analysis of legal education around the globe. In conclusion the article through the lens of cross-border legal education finds that there is a gap in repositioning the Nigerian lawyer through mandatory continuing legal education since it has remained a figment of imagination ever since it evolved. This article is expected to provide an understanding of the appropriate form of legal education for Nigerian lawyers to face contemporary challenges in the competitive market for lawyers.